Estudio de prefactibilidad para la instalación de una planta de producción de envases biodegradables a base de residuos de plátano - Cervantes Cerna, Jose Rodrigo (2022)
This project details the production of biodegradable packaging based on natural products such as banana peel in order to have one more alternative to the use of plastics and avoid the contamination that plastic bags produce in the environment. For the present project, the problem of plastic pollution on the planet and the search for a product that serves as a replacement for the plastic bags so used nowadays, where the market research of the man raw material is taken it will be the banana peel, more precisely in the demand for bananas in Peru, where production has been on the rise in recent years. After having the product established, the Details of it will be established and the 5 Porter´s forces that our product could have will be analyzed. Following this, the specific pobjetives and general objective of the Project and the technical, economic, social and environmental justifications that will be necessary for the development of the product will be raised. In the next chapter, a diagram of operations of the product will have all the detailed processes. Finally, the following chapters are based on presenting the capacity of the plant, the organization chart, the elaboration of the floor plan, the respective financial and economic calculations its evaluations to determinate the viability of the Project.